"Why can't this work here?": social innovation and collective impact in a micropolitan community. Issue 4 (7th August 2020) - Zuckerman, Sarah J.
ABSTRACT: Cross-sector partnerships, and collective impact, in particular, have gained increased attention as community-level strategies for tackling wicked, complex, social challenges such as child maltreatment. To date, there has been limited independent research on collective impact, especially in non-metropolitan areas with limited capacity. This case study examines the conditions that supported the development of a collective impact effort in a non-metropolitan community to address child wellbeing. It finds that small communities offer strengths that support collective impact as a social innovation as well as challenges that create vulnerabilities to outside influence that may stymie the development of locally developed social innovations.